2018
DOI: 10.3389/fphys.2018.01519
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injury Induces Dynamic Changes of Tight Junction Components

Abstract: Tight junctions seal off physical barriers, regulate fluid and solute flow, and protect the endoneurial microenvironment of the peripheral nervous system. Physical barriers in the peripheral nervous system were disrupted after nerve injury. However, the dynamic changes of tight junction components after peripheral nerve injury have not been fully determined yet. In the current study, by using previously obtained deep sequencing outcomes and bioinformatic tools, we found that tight junction signaling pathway wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In vivo studies in mutants lacking MMP-9 indicate that MMP-9 activity during axonal degeneration is crucial to promote myelin sheath collapse and to prompt the blood-nerve-barrier breakdown allowing the influx of immune cells into the nerve (Shubayev and Myers, 2000; Chattopadhyay et al, 2007; Kobayashi et al, 2008). More recent studies have implicated also MMP-9, together with MMP-7, in regulating claudin proteins expression at the tight junction in nerves after crush injury, suggesting that high levels of MMPs might alter nerve physical barriers (Wang et al, 2018). Further, MMP-9 stimulates the rearrangement of the basal lamina (La Fleur et al, 1996; Hartung and Kieseier, 2000; Platt et al, 2003; Shubayev et al, 2006; Chattopadhyay et al, 2007; Kobayashi et al, 2008).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…In vivo studies in mutants lacking MMP-9 indicate that MMP-9 activity during axonal degeneration is crucial to promote myelin sheath collapse and to prompt the blood-nerve-barrier breakdown allowing the influx of immune cells into the nerve (Shubayev and Myers, 2000; Chattopadhyay et al, 2007; Kobayashi et al, 2008). More recent studies have implicated also MMP-9, together with MMP-7, in regulating claudin proteins expression at the tight junction in nerves after crush injury, suggesting that high levels of MMPs might alter nerve physical barriers (Wang et al, 2018). Further, MMP-9 stimulates the rearrangement of the basal lamina (La Fleur et al, 1996; Hartung and Kieseier, 2000; Platt et al, 2003; Shubayev et al, 2006; Chattopadhyay et al, 2007; Kobayashi et al, 2008).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Tight junctions might be related to these findings because reports in the field of dermatology have shown that tight junctions in the skin epithelium are disrupted by neuropathy [26]. However, this requires further research.…”
Section: Discussionmentioning
confidence: 92%
“…The improving effects of A. oxyphylla and Schisandra chinensis (Schisandraceae) fruit (1:1) extract (chloroform fraction of 95% ethanol extract, 1200 mg/kg, orally administered for 30 days) were evaluated using scopolamine (3 mg/kg for nine days) to induce learning and memory impairments in an AD mouse model (Wang et al, 2018). After, Y-maze test and Morris water maze test were carried out to observe the behavior of KM mice.…”
Section: )mentioning
confidence: 99%
“…In addition, the treatment with the extract was able to increase the level of ACh and M1 receptors, and decrease AChE activity, but it did not affect choline acetyltransferase activity. The authors hypothesized that the extract may interfere in the Aβ pathological mechanism, and then play a role in neuroprotective effects on AD (Wang et al, 2018).…”
Section: )mentioning
confidence: 99%